1975
DOI: 10.1007/bf00331455
|View full text |Cite
|
Sign up to set email alerts
|

Specific cross-linking of proteins S7 and L4 to ribosomal RNA, by UV irradiation of Escherichia coli ribosomal subunits

Abstract: Radioactive 30S and 50S subunits from E. coli ribosomes were irradiated with UV light, under conditions giving rise to approximately 10% cross-linking of protein to ribosomal RNA. Irradiation to levels of cross-linking higher than 10% caused unfolding of the ribosomal subunits, even in the presence of 5 mM magnesium. The specificity of the cross-linking reaction at this low level was found to be extremely high. Cross-linked RNA-protein complexes, freed from unbound protein, were treated with nuclease and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…For analysis of the percentage of RNA-protein cross-linking, reaction mixtures containing about 2 A260 units of radioactive subunits were submitted to electrophoresis on 3 % polyacrylamide gels containing 0.1 sodium dodecyl sulphate, exactly as described elsewhere [13].…”
Section: Incubation With Formaldehydementioning
confidence: 99%
See 3 more Smart Citations
“…For analysis of the percentage of RNA-protein cross-linking, reaction mixtures containing about 2 A260 units of radioactive subunits were submitted to electrophoresis on 3 % polyacrylamide gels containing 0.1 sodium dodecyl sulphate, exactly as described elsewhere [13].…”
Section: Incubation With Formaldehydementioning
confidence: 99%
“…Reaction mixtures containing approximately 3 A260 units of radioactive subunits and 300 A260 units of unlabelled subunits were incubated with formaldehyde as above (0.03:d and O.lO%, for 3 0 3 and 50-S subunits, respectively), and the subunits were then precipitated with ethanol before applying to 7.5 -30 % sucrose gradients containing 0.1 % dodecyl sulphate, as described [13]. In this case however, the gradients were run in triethanolamine-HC1 buffer instead of Tris-HC1.…”
Section: Analysis Of Cross-linked Proteins On Two-dimensional Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…eEF-Tu from mRNP. Other investigators have found that UV crosslinking to RNA results in a slight increase in the apparent size of proteins even after RNase digestion [15,16]. On the basis of these data it seems likely that mRNA in rabbit reticulocytes is associated with eEF-Tu.…”
Section: Conmentioning
confidence: 82%